Pendampingan Transformasi Digital Pemasaran UMKM Berbasis Potensi Lokal melalui Program Magang PKKM di Desa Bongo - Lukman Pakaya; Ayu Rakhma Wuryandini; Titi Umi Kalsum Hulopi (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital marketing transformation is an important strategy for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), particularly in rural areas that still face limitations in digital literacy. Bongo Village, located in Batudaa Pantai District, Gorontalo Regency, possesses significant local economic potential through its traditional culinary products and local handicrafts; however, the utilization of digital technology for marketing purposes remains suboptimal. This activity aims to describe the implementation of digital marketing transformation assistance for MSMEs based on local potential through the Merdeka Campus Competition Program (PKKM) Internship Program in Bongo Village. The study employed a Participatory Action Research (PAR) approach consisting of planning, action, observation, analysis, and reflection stages. The program involved 15 Accounting students who acted as facilitators in conducting observations, identifying problems, providing digital marketing assistance, and evaluating the program. The results indicate that the assistance program successfully improved MSME actors’ understanding of the importance of utilizing digital media as a promotional tool, strengthened awareness of local product branding, and increased business actors’ motivation to adopt digital-based marketing strategies. Nevertheless, limited digital literacy and technical capabilities among community members remain significant challenges to achieving optimal digital transformation. Therefore, continuous assistance through collaboration among higher education institutions, village governments, and local communities is necessary to support the sustainable strengthening of MSMEs’ digital capacities